In memoriam Alexander Putchkov (05.09.1954–30.04.2021) - Markina, T. Yu.; Meshkova, V. L.; Shatrovskiy, A. G.; Vovk, D. V. (The Kharkiv Entomological Society Gazette, 2022)
The main points of the biography of the famous Ukrainian entomologist Alexander Putchkov are presented. The results of his scientific, social and organizational work are summed up. The list of the 142 main scientific publications of A. Putchkov are attached. 1 fig.